Alleviating the performance degradation of fuel cells caused by the uneven distribution of internal physical fields. (1st December 2020) - Yuan, Wei-Wei; Ou, Kai; Kim, Young-Bae
Graphical abstract: Highlights: 3-D CFD model is developed to show the uneven distribution of reactants. Interchangeable anode inlet and outlet is proposed to alleviate the uneven distribution. Real experiment results prove the effectiveness of alleviating the fuel cell degradation. Abstract: The performance degradation of proton exchange membrane (PEM) fuel cells is inevitable in real-time application. In particular, water management issues are related to the optimization design and the stable operation of the fuel cell system. The investigation of the mass transportation of an open-cathode PEM fuel cell based on a three-dimensional numerical model is emulated using computational fluid mechanics (CFD). The unified finite element analysis for the coupled phenomena of the charge transport, mass transport, and electrochemical reactions is discussed in this work. The simulation results are observed and compared with other experimental observations and various physical fields have shown uneven distributed inside of the fuel cell due to the single-direction gases transfer strategy. Therefore, in this study, a strategy based on interchangeable anode inlet and outlet is proposed to alleviate the uneven distribution of internal physical fields. Moreover, the optimized periods of inlet and outlet exchange are studied by comparing the experimental results.